2013
DOI: 10.1007/s10903-013-9942-1
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Migration: Depression, Alcohol Abuse, and Access to Health Care Among Migrants in Central Asia

Abstract: Background One fifth of Kazakhstan’s population is labor migrants working in poor conditions with limited legal rights. This paper examines self-rated health, mental health and access to health care among migrant workers. Methods Using geo-mapping, a random sample of internal and external migrant market workers was selected in Almaty (N=450). We used survey logistic regression adjusted for clustering of workers within stalls. Results Almost half of participants described their health as fair or poor and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 57 publications
3
64
1
Order By: Relevance
“…We previously reported that high mobility was associated with poor utilization of health care services in this population (Ismayilova et al 2014). Internal migrants may be as much at risk as external migrants because in Kazakhstan health care access is linked to the specific location of legal residency.…”
Section: Discussionmentioning
confidence: 77%
“…We previously reported that high mobility was associated with poor utilization of health care services in this population (Ismayilova et al 2014). Internal migrants may be as much at risk as external migrants because in Kazakhstan health care access is linked to the specific location of legal residency.…”
Section: Discussionmentioning
confidence: 77%
“…In the fSU and Kazakhstan, depression has also been found to be associated with mobility (Ismayilova et al, 2014) and social isolation (Goryakin et al, 2013; Roberts et al, 2010). Research has also identified associations between depression and food insecurity (Vogenthaler et al, 2011; Weiser et al, 2011) and poor access to health care (Bhatia, Hartman, Kallen, Graham, & Giordano, 2011)…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a meta-analytic review, it was shown that the prevalence of depressive symptoms in China was 2.3% for 12-months and 3.3% for lifetime respectively (Gu et al, 2013). In comparison, Chinese migrants were more vulnerable to depression, with a prevalence between 12.8% to 21.4% (Mou et al, 2011;Qiu et al, 2011;Wong, He, Leung, Lau, & Chang, 2008).Migrant communities are exposed to social and environmental factors that may lead to poor mental health (Ismayilova et al, 2014;Li et al, 2009;Lu, Hu, & Treiman, 2012;Mou et al, 2011;Qiu et al, 2011). Among the multiple factors affecting mental health, migrant status appears to be associated to depression substantially and uniquely in China due to the household registration system, or 'hukou' system.…”
mentioning
confidence: 99%
“…The system divides people into two kinds of citizenship: 'agricultural' and 'non-agricultural' (Wu & Treiman, 2004). Although people from rural areas are able to move to urban areas for economic advantages, jobs, and increased chances for social mobility, they might be exposed to risk factors such as interpersonal violence and perceived discrimination that lead to poorer mental health (Teng, Hall, & Li, 2014;Lin et al, 2011).Several studies conducted in China and elsewhere suggest that when people migrate to other cities or countries they are at increased risk for poor mental health (Ismayilova et al, 2014;Li et al, 2009;Lu et al, 2012;Mou et al, 2011;Qiu et al, 2011). Aside from individual-level risk factors such as gender, marital status, age, education level, and employment status (Li, Stanton, Fang, & Lin, 2006;Li et al, 2009), the lack of adequate social network supports are implicated in poor mental health following numerous life adversities, including migration (Záleská, Brabcová, & Vacková, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation